Fostering Elementary School Students’ Self-Regulation Skills in Reading Comprehension: Effects on Text Comprehension, Strategy Use, and Self-Efficacy - Irini Dermitzaki (Behavioral Sciences)
It has been maintained that active strategic reading is beneficial for students’ reading comprehension (RC) and has cognitive, motivational, and behavioral benefits for students. The aim of the present study was to implement and evaluate the effectiveness of a self-regulation skills training program with a focus on RC for elementary school students. One hundred and nine students (60 girls) from 5th and 6th grade were randomly assigned to an experimental (EG) and a control group (CG). The EG (n = 54) took an intervention program aiming at fostering students’ cognitive and metacognitive strategies to control and regulate the RC process. Before and after the intervention, students’ performance in RC, reported use of strategies for RC, and self-efficacy regarding RC were assessed. The analyses of the data showed that, after the intervention, the EG’s reported strategy use and RC performance were significantly improved in comparison to the CG. Students’ self-efficacy regarding RC did not improve significantly in either group, indicating that in order to increase self-efficacy for RC longer-term interventions might be needed. A follow-up three months after the intervention attested to the maintenance of the core elements of the training program. The findings of the study are discussed within the socio-cognitive approach of self-regulated learning.